State-selective dissociation dynamics of an oxygen molecular ion studied with single-harmonic pump and infrared-probe pulses - Malakar, Y.; Wilhelm, F.; Trabert, D.; P., Kanaka Raju; Li, X.; Pearson, W. L.; Cao, W.; Kaderiya, B.; Ben-Itzhak, I.; Rudenko, A. (My University, 2018)
Laser-induced dissociation of a photoionized oxygen molecule is studied employing an extreme-ultraviolet-pump–near-infrared-probe (EUV-NIR pump-probe) technique. A combination of a narrow-band 11th harmonic pump centered at 17.3 eV and a moderate-intensity NIR probe restricts the dissociation dynamics to the pair of low-lying cationic states, a4Πu and f4Πg. The measured kinetic energies of the O+ fragments reveal contributions from one-, two-, and three-photon dissociation pathways (1ω, 2ω, and 3ω) involving these two states. While the yields of the two- and three-photon channels initially rise and then decrease as a function of EUV-NIR delay, the yield of the single-photon pathway rises slower but keeps increasing over the whole delay range studied. This behavior reflects the evolving probability density of the ionic nuclear wave packet at the internuclear distances, where it can undergo resonant 3ω and 1ω transitions from the a4Πu to the f4Πg state of O2+.
Citation: Malakar, Y., Wilhelm, F., Trabert, D., P., K. R., Li, X., Pearson, W. L., … Rudenko, A. (2018). State-selective dissociation dynamics of an oxygen molecular ion studied with single-harmonic pump and infrared-probe pulses. Physical Review A, 98(1), 013418. https://doi.org/10.1103/PhysRevA.98.013418
Keywords: Atomic & molecular processes in external fields; Photodissociation; Ultrafast phenomena